The Islami Information Technology Strategic Planning Model - Slamet Slamet (Seminar Nasional Informatika (SEMNASIF), 2020)
AbstractThis study's main objective is to develop a strategic planning model in Islami's information technology field. This objective is based on the study results that public organizations lack a strategic planning process and still experience a high percentage of failures. This failure was due to a lack of attention to human and organizational social factors in the strategic planning process. The study method is mix-method by a research and development approach. Source of data is primer. The data collection technique used a survey and focus group discussion. The instrument is researchers themselves and questionnaire. The stages of the study include literature review, analysis of the ITSP model, design of the ITSP model draft, FGD group discussion and revision of the information ITSP model draft, and testing and approval of the ITSP model. Data analysis using qualitative and quantitative analysis approaches. The finding is that people involved in Islamic universities are more respectful of more Islamic statements and promote Islamic values. The development results of the model consists are five stages, namely developing ideas, determining the direction, assessment and analysis, determining strategic decisions, and implementation plan. Each stage is controlled by Islamic principles and values.Keywords: model, information technology, strategic planning, islamic principles and values.Tujuan utama penelitian ini adalah untuk mengembangkan model perencanaan strategik di bidang teknologi informasi yang mengedepankan prinsip dan nilai-nilai Islam dalam prosesnya. Tujuan ini didasarkan pada hasil studi bahwa organisasi publik kurang memiliki proses perencanaan strategik dalam bidang teknologi informasi dan dilaporkan masih mengalami persentase kegagalan yang tinggi. Kegagalan ini disebabkan kurangnya perhatian pada faktor sosial manusia dan organisasi dalam proses perencanaan strategik. Metode penelitian yang digunakan adalah metode campuran dengan pendekatan penelitian dan pengembangan. Sumber data adalah primer. Teknik pengumpulan data menggunakan survei dan focus group discussion. Instrumennya adalah peneliti sendiri dan angket. Tahapan penelitian meliputi tinjauan pustaka, analisis model perencanaan strategik teknologi informasi, perancangan draf model perencanaan strategik teknologi informasi, focus group discussion dan revisi draf model perencanaan strategik teknologi informasi, dan pengujian dan persetujuan model perencanaan strategik teknologi informasi. Analisis data menggunakan pendekatan analisis kualitatif dan kuantitatif. Temuan kajian yaitu bahwa orang-orang yang terlibat di universitas Islam lebih mengapresiasi pernyataan Islam dan mengedepankan prinsip dan nilai-nilai Islam. Hasil pengembangan model terdiri dari lima tahap yaitu pengembangan ide, penentuan arah, penilaian dan analisis, penentuan keputusan strategis, dan rencana implementasi. Masing-masing tahapan dikontrol oleh prinsip dan nilai Islam.Kata Kunci: model, teknologi informasi, perencanaan strategik, prinsip dan nilai Islam.